Management verschiedener kardiovaskulärer Risikofaktoren mit einem Kombinationspräparat („Polypill“) - Bramlage, Peter; März, Winfried; Krämer, Bernhard (Herz, 2018)
Background: The multifactorial origin of cardiovascular diseases has led to polypharmacy in primary and secondary prophylaxis with evidence-based medications, such as statins, antihypertensive drugs and platelet aggregation inhibitors. The number of prescribed drugs correlates inversely to adherence and can lead to treatment failure. Fixed-dose combination drugs (polypills) could increase the medication adherence of patients, reduce risks and prevent cardiovascular events. Methods: This review is based on publications that were retrieved from Medline (via PubMed) and The Cochrane Library. The clinical database ClinicalTrials.gov. was also considered. Results: In the studies on primary prevention conducted to date, fixed-dose combinations showed a superior control of risk factors, e.g. hypertension and low-density lipoprotein (LDL) cholesterol compared to placebo and at least non-inferiority compared to usual care. In secondary prevention, the effect of the polypill is mostly on the reduction of blood pressure and LDL cholesterol in non-adherent patients; however, evidence that fixed-drug combinations reduce cardiovascular morbidity and mortality compared to standard therapy is lacking. Conclusion: The polypill can be considered as an alternative to polypharmacy after a risk-benefit assessment, especially in non-adherent patients. Ongoing studies are investigating the effect of the polypill on cardiovascular events. Current polypills are limited by the lack of sufficient dosages of the individual components to avoid overtreatment and undertreatment at the individual treatment level.
Online publiziert: 24. März 2017
Gesehen am 29.07.2019